Reperfusion in non-occlusive mesenteric ischaemia (NOMI): effectiveness of CT in an emergency setting - Mazzei, Maria A (Br J Radiol, 2016)
OBJECTIVE: To investigate the CT features of reperfusion (presence/absence) in non-occlusive mesenteric ischaemia (NOMI) and their prognostic value in an emergency setting. METHODS: A revision was undertaken of imaging from 20 patients (16 males/4 females) with a dismissal summary of NOMI. All patients had previously undergone a minimum of one multidetector CT examination, and consequently underwent surgery (n = 8), autopsy (n = 2), angiography (n = 1) or endoscopy (n = 9). An evaluation of the CT scans was conducted to determine vessels, mesentery, bowel and peritoneal cavity features. The superior mesenteric artery (SMA) average diameter of NOMI cases were compared with 30 controlled cases. Kappa, Kolmogorov–Smirnov (K-S) and Fisher's exact tests were used for statistical analysis. RESULTS: A mean SMA diameter significantly smaller than that of the controlled cases was found for patients with NOMI (K-S test: D = 0.75, p = 3.7 × 10-08). Fisher's exact tests showed a strong connection between the presence of reperfusion and mesenteric fat stranding (p = 0.026), bowel wall thickening (p = 3.2 × 10-05) and a high attenuation of the bowel wall on unenhanced CT images (p = 2.8 × 10-04). A reduction in mortality was significantly linked to the combination of normal mesenteric vessels and wall thickening (p = 0.034). CONCLUSION: Analysis of not only vessels findings but also mesentery and bowel CT features will support the identification of NOMI with or without a reperfusion event in an emergency setting. A strong correlation between some CT features and lower mortality exists. ADVANCES IN KNOWLEDGE: CT features of NOMI with or without reperfusion are demonstrated. Correctly assessing the presence of reperfusion in NOMI, may allow better management of these conditions in the emergency setting.